Role of Interleukin-10 in Malaria: Focusing on Coinfection with Lethal and Nonlethal Murine Malaria Parasites. (18th September 2011) - Niikura, Mamoru; Inoue, Shin-Ichi; Kobayashi, Fumie
Abstract : Interleukin- (IL-) 10, anti-inflammatory cytokine, is known to inhibit the protective immune responses against malaria parasites and to be involved in exacerbating parasitemia during Plasmodium infection. In contrast, IL-10 is regarded as necessary for suppressing severe pathology during Plasmodium infection. Here, we summarize the role of IL-10 during murine malaria infection, focusing especially on coinfection with lethal and nonlethal strains of malaria parasites. Recent studies have demonstrated that the major sources of IL-10 are subpopulations of CD4 + T cells in humans and mice infected with Plasmodium . We also discuss the influence of innate immunity on the induction of CD4 + T cells during murine malaria coinfection.